Analisis Penerapan Prinsip Hotel Syariah Pada Hotel Satria Syariah Batusangkar - Yunita Nurharani; Pepy Afrilian; Muhammad Deni Putra (i-Tourism: Jurnal Pariwisata Syariah, 2021)
The main problem in this thesis is that there are differences in the application and there has been no implementation of sharia principles at the Satria Syariah Batusangkar Hotel. This hotel was only established as a guest house in 2016, then renovated and made into a hotel in 2019. The purpose of this study was to analyze the application of sharia at the Satria Syariah Batusangkar hotel with the tourism and creative economy PERMEN approach number 2 in 2014.The type of research that the author uses is field research, in this study the author will discuss the differences in the application and what sharia principles have not been applied to at the Hotel Satria Syariah Batusangkar based on PERMEN tourism and creative economy number 2 of 2014. Data collection techniques used the authors use is through observation, interviews, and documentation. Data processing was carried out in a qualitative descriptive manner.From the research that the author conducted in the field, it can be concluded that, from the aspect of management, product, service according to the new moon 1 (which is absolute) there are still differences in the application or even not applying sharia principles at all, the first aspect of management is business management, the second aspect products, namely public toilets, kitchens, and prayer rooms. The three service aspects are housekeeping, food and beverages. Based on the results of the SWOT analysis using a graph, it can be concluded that the hotel is in quadrant 3 which means it has a very large opportunity from the outside environment in the application of sharia principles but the hotel has weaknesses from the internal resources of the hitel itself. The focus of a hotel's strategy in this condition should be to eliminate internal weaknesses so that it can concentrate on pursuing available environmental opportunities in order to implement sharia principles.